Reducing Inequity in Urban Health: Have the Intra-urban Differentials in Reproductive Health Service Utilization and Child Nutritional Outcome Narrowed in Bangladesh? - Angeles, Gustavo (J Urban Health, 2018)
Bangladesh is undergoing a rapid urbanization process. About one-third of the population of major cities in the country live in slums, which are areas that exhibit pronounced concentrations of factors that negatively affect health and nutrition. People living in slums face greater challenge to improve their health than other parts of the country, which fuels the growing intra-urban health inequities. Two rounds of the Bangladesh Urban Health Survey (UHS), conducted in 2013 and 2006, were designed to examine the reproductive health status and service utilization between slum and non-slum residents. We applied an adaptation of the difference-in-differences (DID) model to pooled data from the 2006 and 2013 UHS rounds to examine changes over time in intra-urban differences between slums and non-slums in key health outcomes and service utilization and to identify the factors associated with the reduction in intra-urban gaps. In terms of change in intra-urban differentials during 2006–2013, DID regression analysis estimated that the gap between slums and non-slums for skilled birth attendant (SBA) during delivery significantly decreased. DID regression analysis also estimated that the gap between slums and non-slums for use of modern contraceptives among currently married women also narrowed significantly, and the gap reversed in favor of slums. However, the DID estimates indicate a small but not statistically significant reduction in the gap between slums and non-slums for child nutritional status. Results from extended DID regression model indicate that availability of community health workers in urban areas appears to have played a significant role in reducing the gap in SBA. The urban population in Bangladesh is expected to grow rapidly in the coming decades. Wide disparities between urban slums and non-slums can potentially push country performance off track during the post-2015 era, unless the specific health needs of the expanding slum communities are addressed. To our knowledge, this is the first systematic explanation and quantification of the role of various factors for improving intra-urban health equity in Bangladesh using nationally representative data. The findings provide a strong rationale for continuing and expanding community-based reproductive health services in urban areas by the NGOs with a focus on slum populations.